La seguridad jurídica y la atribución de los notarios para solemnizar la partición de bienes hereditarios - Sarmiento Bustamante, Vinicio Leonardo (2023)
The death of a person is a legal fact that generates important consequences, one of them is to solve the patrimonial situation, the destiny of the assets that were owned by the deceased, purpose for which the Ecuadorian legislation incorporates the succession by cause of death that implies the transfer of domain of such assets in favor of the heirs or legatees of the deceased, circumstance in which the partition must be celebrated. This paper deals with the voluntary extrajudicial partition in notarial venue, and in relation to it, the problem related to the requirement of a solemn judicial inventory as a prerequisite, since the civil and notarial regulations are not clear in this regard, which has generated conflicting criteria among lawyers, notaries and property registrars. In view of the above, this article is developed, reaching important conclusions in the sense that the notarial should be applied according to the free will of the heirs and relying on a less solemn inventory presented by the interested parties, and that the legislative framework should be adapted to be clear and coherent in order to guarantee legal certainty to all those involved.